Theoretical Possibilities of Controlling the Cooling Rate in the Heat Treatment of Cast Iron with Water Mist - Stręk, Piotr (Journal of Casting & Materials Engineering, 2024)
The goal of the cooling procedure after austenitizing in the austempering heat treatment process applied to ausferritic ductile iron (ADI) castings is to rapidly reduce the temperature throughout the casting volume to the temperature range of the process window in which the proper metal matrix structure is formed. The lower limit of this range must be higher than the temperature at which the martensitic transformation starts. The upper limit is selected to eliminate the possibility of diffusion decomposition of austenite while holding castings at austempering temperature. Most often in heat treatment practice, salt baths are used for this purpose. Such a solution makes it possible to realize in one device both the procedure of cooling down to a given temperature and the procedure of isothermal heat treatment at this temperature. Unfortunately, the presence of molten salt in the process equipment has a very unfavorable impact on working conditions and ecology. The purpose of this research is to analyze the possibility of replacing the salt bath cooling procedure in the manufacturing process of ADI castings with a water mist spray cooling procedure on the surfaces of the heat-treated casting. If such cooling is effective, subsequent procedures of heat treatment operations can be carried out with traditional furnace equipment without the use of molten salt, which will clearly improve the environmental performance of the enterprise. The article, using analytical and numerical methods, analyzes the possibility of cooling objects made of cast iron with the help of a high-efficiency heat receiver such as water mist spraying. The limiting conditions for carrying out the process for the assumed cooling curve were considered. It was proposed to use a PID controller realizing the function of controlling the intensity of water mist spray, which corresponds to the intensity of the heat flux received from the heat-treated casting. The theoretical analysis carried out allows us to conclude that water mist cooling according to the assumed cooling curve is practically feasible.